2012
DOI: 10.4321/s0213-61632012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and common mental disorders in the community: Results of the Israel-World Mental Health Survey

Abstract: -Background and Objectives: To study common mental disorders (CMD) and other mental health-related variables among community residents with active cancer, cancer survivors and cancer-free respondents.Methods: Data were extracted from the Israeli component of the 28-country World Mental Health Survey. The sample included 165 respondents who reported ever having cancer and 2,282 cancer-free respondents, all aged 39 years and older. The WHO/Composite International Diagnostic Interview (CIDI) was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…The results showed elevated risk of comorbid common mental health disorders among persons who at the time of the study were undergoing treatment for cancer across all countries studied compared with either cancer survivors or cancer-free respondents. Our findings thus confirm the results of the few prior communitybased studies that found high rates of comorbid mental disorders among people with active cancer [8,10]. Notably, the comorbidity rates were lower in our study than in a previous study conducted in the US, the National Comorbidity Survey (NCS) [10], likely because the current study included respondents spanning the full adult age range (compared with a restricted age range of 15-54 in the NCS) and from a wide range of countries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed elevated risk of comorbid common mental health disorders among persons who at the time of the study were undergoing treatment for cancer across all countries studied compared with either cancer survivors or cancer-free respondents. Our findings thus confirm the results of the few prior communitybased studies that found high rates of comorbid mental disorders among people with active cancer [8,10]. Notably, the comorbidity rates were lower in our study than in a previous study conducted in the US, the National Comorbidity Survey (NCS) [10], likely because the current study included respondents spanning the full adult age range (compared with a restricted age range of 15-54 in the NCS) and from a wide range of countries.…”
Section: Discussionsupporting
confidence: 90%
“…A significant proportion of persons with cancer at different stages of the disease trajectory develop mental disorders, primarily affective and anxiety disorders (henceforth, common mental disorders) . In this paper, we examined the comorbidity of common mental disorders and cancer and their respective mental health treatment gap (i.e., the proportion of individuals with active cancer and a mental disorder who have received no treatment for their mental disorder).…”
Section: Introductionmentioning
confidence: 99%
“…During treatment, cancer patients can suffer substantial physical and psychological distress and are at an increased risk for suicide (Massie, 2004;Miovic & Block, 2007;Nakash, Barchana, Liphshitz, Keinan-Boker, & Levav, 2012;Singer, Das-Munshi, & Brähler, 2009). Approximately onethird of persons with cancer will develop a mood or anxiety disorder (Grassi, Caruso, Sabato, Massarenti, & Nanni, 2015;Miovic & Block, 2007;Mitchell et al, 2011;Nakash, Liphshitz, Keinan-Boker, & Levav, 2013;Nakash, Shemesh, Nagar, & Levav, 2012;Nakash et al, 2014;Singer et al, 2009). Findings from a recent study based on data from the World Mental Health Surveys from 13 high-and 11 low-middleincome countries showed that 12-month prevalence rates of mood and anxiety disorders were higher among active cancer patients (18.4%) compared with cancer-free respondents (13.3%) (Nakash et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Those findings have shown that members of socially disadvantaged groups (e.g., ethnic minorities) are at higher risk for mental and behavioral disorders compared with members of advantaged groups [ 15 , 16 ], thus creating a residue of vulnerable populations whose mental health risk may cross generations [ 17 ]. Importantly as well, studies have found that the treatment gap (i.e., the proportion of individuals with a diagnosable mental disorder who do not receive treatment) is high [ 18 – 20 ], including among vulnerable population groups [ 21 , 22 ]. With regard to children, the treatment gap is even higher than among adults [ 23 ].…”
Section: Discussionmentioning
confidence: 99%